The Influence of Brand Awareness, Perceived Quality, Brand Association, Brand Loyalty and Price on Daihatsu Car Buying Decisions (Case Study at Daihatsu Pemalang Car Dealership) - Mar’atus Solikhah; Amelia Amelia (Publikasi Indonesia, 2023)
The purpose of this study to find and obtain empirical evidence of the influence of brand awareness, perceived quality, brand association, brand loyalty, and price on buying decisions both partially and simultaneously. This study uses a sample of 70 respondents, namely some of consumers who buy Daihatsu cars at Pemalang Daihatsu Dealers. The sample used was using purposive sampling technique. The testing in this study was carried out using instrument test analysis methods such as validity, reliability, classic assumption tests such as normality tests, linearity tests, and heterogedity tests, and on statistical tests such as path analysis, multiple linear regression, t-test, F test. The results of this study were obtained 1) there is a significant influence between brand awareness variables (X1) on purchasing decisions (Y); 2) there is a significant influence between the perceived quality variable (X2) on purchasing decisions (Y); 3) there is a significant influence between brand association variables (X3) on purchasing decisions (Y); 4) there is a significant influence between brand loyalty variables (X4) on purchasing decisions (Y); 5) there is a significant influence between the price variable (price) (X5) on the purchase decision (Y); 6) brand awareness variables (X1), perceived quality (X2), brand associations (X3), brand loyalty (X4), and price (X5) partially influence purchasing decisions (Y); 7) variable brand awareness (X1), perceived quality (X2), brand association (X3), brand loyalty (X4), and price (X5) simultaneously influence purchasing decisions (Y);